DISCOVERING THE MEANING OF SIGNS IN PUBLIC SERVICE ADVERTISEMENTS - I Wayan Juniartha; I Komang Sulatra; AAA Dian Andriyani (Translation and Linguistics (Transling), 2022)
This study concerns in analysing the meaning of verbal and visual signs in four Public Service advertisements. This study aims to find out the verbal and visual sign as tool in discovering the meaning related to important issues occurred in the society recently. The method used in analysing data is qualitative method in order to conduct a clear and well-organized description about the phenomena which is being identified. Furthermore, descriptive study in textual analysis is applied to analyse the signs used in the public service advertisement. This study applied the theory of sign element by Saussure (1983) and theory of meaning by Chandler (2007). The finding shown that there were purposes of warn, reminding people to do positive thing related to the topic of advertisement which is shown by the object, such as: human, buildings, cars, photos or images, colour, smartphones, as well as sentences and coloured word used in the advertisement. The discovered meaning in this study has successfully shown the issues that is occurred in the society which gives the impact for the audiences in emerging the sense of empathy of the issue itself.